Bijaksana dalam menggunakan media sosial dengan berlandaskan Al-Qur'an untuk mencegah dampak yang mengerikan - Saputra, M Hendra (Maliki Interdisciplinary Journal, 2024)
Living in the digital era is a challenge and an extraordinary thing that is lived by humans in this day and age, let's call it social media with the various features and sophistication offered to make all life arrangements easier to run, but it doesn't stop there behind the amazing things that promised by social media, it still has a terrible impact. Indonesia as the fourth most populous country in the world, the same rank is also obtained by Indosia as the fourth most internet user country in the world, of course many things and problems have occurred in countries that this is rich. Hoaxes are one of the problems of the many negative impacts of social media, news that can cause division and even war. Hoax news at this time may have spread everywhere, that's why the author wants to give a little explanation of how dangerous social media is if you are not wise in using it. using it includes how it is not easy to receive news that is feared to contain elements of lies.